2009
DOI: 10.1002/app.30046
|View full text |Cite
|
Sign up to set email alerts
|

Broadband dielectric spectroscopy on the molecular dynamics in different generations of hyperbranched polyester

Abstract: Dielectric spectroscopy (10 À2 Hz to 10 6 Hz) was employed to investigate the molecular dynamics of hyperbranched polyesters where the number of the generation is systematically varied from 2 to 5. As a first result, the dielectric properties depends strongly on the generation of the hyperbranched polymers. For higher generations (3 to 5) at temperatures below T g two relaxation processes are observed, a c-process at lower temperatures and a b-process at higher ones. The apparent activation energies are around… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
38
3
5

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(49 citation statements)
references
References 54 publications
(64 reference statements)
3
38
3
5
Order By: Relevance
“…14 We have selected a particular category of hyperbranched polymers, that of hydroxyl-terminated polyesters, due to their low cost, their wide commercial availability, and the previous knowledge on their physical behavior down to the microscopic scale. 12,31,97,101 Our results showed that at the examined volume fractions, graphene flakes can be present as individual platelets but at most they appear to organize in stacks (Figure 8) comprised by 2−3 flakes (Figures 1 and 9). The presence of graphene dimers and trimers has been correlated with maximization of the composite modulus as a function of the number of graphene flakes in previous studies, 35,90 which in combination with the lower viscosity characterizing the hyperbranched molecules and their thermal stability, render such hybrids ideal candidates for optimization of mechanical response and processability.…”
Section: Discussionmentioning
confidence: 81%
“…14 We have selected a particular category of hyperbranched polymers, that of hydroxyl-terminated polyesters, due to their low cost, their wide commercial availability, and the previous knowledge on their physical behavior down to the microscopic scale. 12,31,97,101 Our results showed that at the examined volume fractions, graphene flakes can be present as individual platelets but at most they appear to organize in stacks (Figure 8) comprised by 2−3 flakes (Figures 1 and 9). The presence of graphene dimers and trimers has been correlated with maximization of the composite modulus as a function of the number of graphene flakes in previous studies, 35,90 which in combination with the lower viscosity characterizing the hyperbranched molecules and their thermal stability, render such hybrids ideal candidates for optimization of mechanical response and processability.…”
Section: Discussionmentioning
confidence: 81%
“…The dielectric dispersion of the aliphatic polyester as a function of frequency in the vicinity of T g relaxation can be described by Havriliak‐Negami (HN) phenomenological equation 34–37. Then, the complex dielectric permittivity ε* is given by: where Δε = ε s − ε ∞ , is the dielectric strength, ε s and ε ∞ are the relaxed and unrelaxed dielectric constants, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…They [52,114] pointed out that the majority of the hydroxyl groups are hydrogen-bonded in four diverse assemblies, differing in strength. The effect of intermolecular and intramolecular interaction caused by the polar groups were investigated experimentally by Turky et al [115] using dielectric spectroscopy and theoretically by Tanis and Karatasos [116] by atomistic molecular dynamics simulation. Both studies [115,116] concluded that the intramolecular interactions are stronger than the intermolecular interactions.…”
Section: Wertheim Theorymentioning
confidence: 99%
“…The effect of intermolecular and intramolecular interaction caused by the polar groups were investigated experimentally by Turky et al [115] using dielectric spectroscopy and theoretically by Tanis and Karatasos [116] by atomistic molecular dynamics simulation. Both studies [115,116] concluded that the intramolecular interactions are stronger than the intermolecular interactions. For this reason intramolecular as well as intermolecular association should be taken into account in the thermodynamic model.…”
Section: Wertheim Theorymentioning
confidence: 99%